Ultrasound-based gestational-age estimation in late pregnancy - Papageorghiou, AT; Kemp, B; Stones, W; Ohuma, EO; Kennedy, SH; Purwar, M; Salomon, LJ; Altman, DG; Noble, JA; Bertino, E; Gravett, MG; Pang, R; et al. (Wiley, 2016)
Objective Accurate gestational-age (GA) estimation, preferably by ultrasound measurement of fetal crown–rump length before 14 weeks' gestation, is an important component of high-quality antenatal care. The objective of this study was to determine how GA can best be estimated by fetal ultrasound for women who present for the first time late in pregnancy with uncertain or unknown menstrual dates.